Promotion of Lactobacillus plantarum on growth and resistance against acute hepatopancreatic necrosis disease pathogens in white-leg shrimp (Litopenaeus vannamei) - Nguyen, Thi Thuy Giang (มหาวิทยาลัยสงขลานครินทร์, 2022)
Acute hepatopancreatic necrosis disease (AHPND), or early mortality syndrome (EMS), causes high mortality in cultivated penaeid shrimps, which leads to heavy losses for shrimp farming industry. V. parahaemolyticus with a toxin PirAB-encoding extrachromosomal plasmid are considered as common pathogenic agents. The present study aimed to assess the effects of potential probiotics on growth and resistance of shrimp to AHPND infection. Results confirmed typical clinical signs and histopathological features in AHPND-infected shrimps. Among 11 Vibrio isolates from AHPND-infected shrimps, strain XN9 was the most virulent and was identified as V. paraheamolyticus using AP3-based PCR amplification and API 20E kits. In vitro screening of potential probiotics was performed based on 26 marine and fermented food-derived bacteriocin-producing bacterial strains with broad inhibitory spectra from our previous research. Among these candidates, only two strains, Lactobacillus plantarum T8 and T13, exerted antimicrobial activities against all tested Vibrio isolates. Further in vitro trials showed that T8 enhanced significant growth and survival of shrimps after bath challenge with XN9. Although it had no significant effect on shrimp growth, T13 expressed better protection of shrimp from the AHPND pathogen immersed compared to the T8 treatment, or the control. This study presents the first evidence on the positive effects of probiotic candidates on growth and resistance of white-leg shrimp against V. paraheamolyticus causing AHPND.